PENGARUH KUALITAS PELAYANAN TERHADAP KEUNGGULAN BERSAING PADA CHAMPION CAFÉ MEDAN - Intan Bona Rejeki Sinaga; Elizabeth Haloho (JURNAL MUTIARA MANAJEMEN, 2020)
This study aims to determine the effect of service quality on competitive advantage at Champion Café Medan. The method used is descriptive quantitative. The data collection technique used a questionnaire and the sampling technique used was random sampling. The sample in this study were 99 respondents or customers of Champion Café Medan. The analysis technique uses multiple regression. The results of this study indicate that (1) there is a positive and significant relationship between tangibles and competitive advantage, where tcount is 11.594, while ttable with N = 99 at the 10% significance level is 1.661, so tcount> ttable (11.594> 1.661). (2) there is a positive and significant relationship between reliability and competitive advantage, where t count is 4.095, while t table with N = 99 at the 10% significance level is 1.661, so tcount> ttable (4.095> 1.661). (3) there is no positive and significant relationship between empathy and competitive advantage, where t count is 0.780, while ttable with N=99 at the 10% significance level is 1.661, so tcount> ttable (0.780 <1.661). (4) there is no positive and significant relationship between responsiveness and competitive advantage, where tcount is -5.429, while ttable with N = 99 at the 10% significance level is 1.661, so tcount> ttable (-5.429 <1.661). (5) there is a positive and significant relationship between assurance and competitive advantage, where tcount is 5.124, while ttable with N = 99 at 10% significance level is 1.661, so tcount> ttable (5.124> 1.661).